Armed with an Eagle Feather Against the Parliamentary Mace: A Discussion of Discourse on Indigenous Sovereignty and Spirituality in a Settler Colonial Canada, 1990-2017 - Swain, Stacie A. (Université d'Ottawa / University of Ottawa, 2017)
Canada 150, or the sesquicentennial anniversary of Confederation, celebrates a nation-state that can be described as “settler colonial” in relation to Indigenous peoples. This thesis brings a Critical Religion and Critical Discourse Analysis methodology into conversation with Settler Colonial and Indigenous Studies to ask: how is Canadian settler colonial sovereignty enacted, and how do Indigenous peoples perform challenges to that sovereignty? The parliamentary mace and the eagle feather are conceptualized as emblematic and condensed metaphors, or metonyms, that assert and represent Canadian and Indigenous sovereignties. As a settler colonial sovereignty, established and naturalized partially through discourses on religion, Canadian sovereignty requires the displacement of Indigenous sovereignty. In events from 1990 to 2017, Indigenous people wielding eagle feathers disrupt Canadian governance and challenge the legitimacy of Canadian sovereignty. Indigenous sovereignty is (re)asserted as identity-based, oppositional, and spiritualized. Discourses on Indigenous sovereignty and spirituality provide categories and concepts through which Indigenous resistance occurs within Canada.
Keywords: Canada; Indigenous Sovereignty; Indigenous Spirituality; Sovereignty; Parliamentary Mace; Eagle Feather; Critical Religion; Critical Discourse Analysis; Settler Colonialism; Religious Studies; Indigenous Resistance; Religion; Elijah Harper; Idle No More; Indigenous-Canadian Relations; Canadian Governance; Indigenous Nationhood; Oka